Exploring Multifunctional Bioactive Components from Podophyllum sinense Using Multi-Target Ultrafiltration - Feng, Huixia; Chen, Guilin; Zhang, Yongli; Guo, Mingquan (Frontiers in Pharmacology, 2021)
Diphylleia sinensis (D. sinensis) has been used as traditional herbal medicine for ages due to its extensive pharmaceutical activities, including anti-proliferative, anti-inflammatory, anti-viral, insecticidal effects, etc. Nevertheless, the specific bioactive constituents responsible for its anti-proliferative, anti-inflammatory and anti-viral activities remain elusive owing to its complicated and diversified chemical components. In order to explore these specific bioactive components and their potential interaction targets, affinity ultrafiltration with multiple drug targets coupled with high performance liquid chromatography / mass spectrometry (UF-HPLC/MS) strategy was developed to rapidly screen out and identify bioactive compounds against four well-known drug targets correlated to their traditional use, namely Topo I, Topo II, COX-2 and ACE2. As a result, 7, 10, 6 and 7 phytochemicals were screened out as the potential Topo I, Topo II, COX-2 and ACE2 ligands, respectively. Further confirmation of these potential bioactive components with anti-proliferative and COX-2 inhibitory assays in vitro was also implemented. Hereinto, diphyllin and podophyllotoxin with higher EF values demonstrated higher inhibitory rates against A549 and HT-29 cells as compared with 5-FU and etoposide. The IC50 values of diphyllin were calculated at 6.46  1.79 M and 30.73  0.56 M on A549 and HT-29 cells, respectively. Moreover, diphyllin exhibited good COX-2 inhibitory activity with the IC50 value at 1.29  0.14 M, whereas indomethacin was 1.22  0.08 M. In addition, those representative constituents with good affinity on Topo I, Topo II, COX-2 or ACE2, such as diphyllin, podophyllotoxin and diphyllin O-glucoside, were further validated with molecular docking analysis. Above all, the integrated method of UF-HPLC/MS with multiple drug targets rapidly singled out multi-target bioactive components, and partly elucidated their action mechanisms regarding its multiple pharmacological effects from medicinal plants, which could provide valuable information about its further development for the new multi-target drug discovery from natural medicines.